Finding HOPE: Changes in depressive symptomology following relocation from distressed public housing. (October 2017) - Webb, Michael D.; Rohe, William M.; Nguyen, Mai Thi; Frescoln, Kirstin; Donegan, Mary; Han, Hye-Sung
Abstract: Many public housing residents suffer from poor mental health and depression, which may be a function of both socioeconomic deprivation and residing in disorderly, unstable, and disadvantaged neighborhoods. While not explicitly targeting mental health, the HOPE VI program may improve public housing residents' mental health by relocating them from distressed developments and into less-disadvantaged and disorderly neighborhoods. This paper examines post-relocation depressive symptomology among residents relocated from the Boulevard Homes public housing development in Charlotte, NC. Drawing on pre- and post-relocation surveys, as well as interviews with staff and case managers, we examine whether depressive symptomology – measured by the CES-D-10 – is associated with whether tenants relocate to other public housing or to private-market housing through the Housing Choice Voucher program. Further, we investigate whether social support, perceptions of safety, or objective neighborhood measures result in improvements in post-relocation depressive symptomology. We find that depressive symptomology substantially decreased following relocation, and those with higher CES-D-10 scores were more likely to move to other public housing rather than through the voucher program. Interviews with case managers suggest that some residents were fearful of leaving public housing and assuming the responsibilities of a private-market rental unit – e.g., basic maintenance and utility payments. Further, we find that reductions in post-relocation depressive symptomology are associated with greater perceptions of safety, greater social support in their new neighborhoods, and length of tenure at Boulevard Homes. Policy recommendations include expanding community-based mental health services, conducting pre-relocation mental health screenings, and providing additional relocation counseling to those suffering from depression. Highlights: Relocation from distressed public housing improves depression rates and intensity. These improvements relate to greater perceived safety and higher social support. We find no relationship between relocation neighborhood attributes and depression. Depressed residents more likely to relocate to other public housing. Results indicate need for greater mental health support to public housing residents.